2023
DOI: 10.1002/pen.26406
|View full text |Cite
|
Sign up to set email alerts
|

A focused review on recycling and hydrolysis techniques of polyethylene terephthalate

Abstract: Polyethylene terephthalate (PET) is used in textile and packaging industries. The main source of PET production is fossil fuels with limited capacity. Also, PET products are single use that transform into high volumes of wastes, causing ecosystem problems. Recycling is proposed to confront this challenge. The four major PET recycling techniques are mechanical, chemical, pyrolysis, and enzymatic. Mechanical, pyrolysis, and enzymatic techniques have constrained capabilities to manage PET waste. Chemical recyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 308 publications
0
23
0
Order By: Relevance
“…Scheme 6 shows the reaction mechanism of PET acid hydrolysis catalysed by protonic acid. 69–71 Concentrated sulphuric acid (Scheme 7) is generally used for acid hydrolysis, and sometimes nitric acid, phosphoric acid, p -toluenesulfonic acid and ethylenediaminetetraacetic acid are also used. 27,72–74 Yoshioka believes that the hydrolysis kinetics of PET in sulphuric acid can be explained by the modified shrinking core model controlled by chemical reactions (Fig.…”
Section: Recycling and Depolymerisation Of Petmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 6 shows the reaction mechanism of PET acid hydrolysis catalysed by protonic acid. 69–71 Concentrated sulphuric acid (Scheme 7) is generally used for acid hydrolysis, and sometimes nitric acid, phosphoric acid, p -toluenesulfonic acid and ethylenediaminetetraacetic acid are also used. 27,72–74 Yoshioka believes that the hydrolysis kinetics of PET in sulphuric acid can be explained by the modified shrinking core model controlled by chemical reactions (Fig.…”
Section: Recycling and Depolymerisation Of Petmentioning
confidence: 99%
“…The mechanism of PET alkaline hydrolysis is shown in Scheme 8. 69,71,78 Usually, a solution of KOH or NaOH with a concentration of 4–20 wt% is used to treat PET waste at 200–250 °C. 12,65,79 In 1959, Pitat published a patent for the alkaline hydrolysis of PET.…”
Section: Recycling and Depolymerisation Of Petmentioning
confidence: 99%
“…126 Abedsoltan reported a detailed insight into hydrolysis of PET including the types and advanced treatment methodologies of the polyester plastic waste. 126 Neutral hydrolysis is used to depolymerize polyester plastic waste in excess water and high temperatures (115−420 °C) and pressures (10−420 atm), without requiring any organic solvent. 4 The kinetics and thermodynamics have been studied by Zope et al, and the frequency factor and activation energy (E a ) were found to be 2.9 × 10 8 min −1 and 9.58 kJ mol −1 , respectively, but no commercial establishment has been done due to harsh conditions and increased operational costs.…”
Section: Recyclingmentioning
confidence: 99%
“…Alkaline PET hydrolysis requires a subsequent acidification process, which is an additional step for TPA recovery not necessary for acid hydrolysis. 11 Although mineral acid catalysts have been extensively studied, their oxidative effect and tendency to cause carbonization decrease product yields. 9,[12][13][14][15] Hydrolysis can take place within 70-100 °C in the presence of highly concentrated sulfuric or nitric acids but the reaction times can extend to several days, presenting various engineering challenges.…”
Section: Introductionmentioning
confidence: 99%